The State of Public Finances Cross-Country Fiscal Monitor : November 2009. (IMF Staff Position Notes; Staff Position Note, 2009)
This paper highlights the state of Public Finances Cross-Country Fiscal Monitor. This edition of the Cross-Country Fiscal Monitor provides an update of global fiscal developments and policy strategies, based on projections from the November 2009 WEO. These projections reflect the assessment of IMF staff of current country policies and initiatives expected during 2009-2014 Underlying fiscal trends in advanced economies are weaker than previously projected, however, lower expected costs of financial sector support in the United States mean that 2009 headline numbers are better. New estimates of needed medium-term fiscal adjustment in advanced economies. Fiscal policy will continue to provide substantial support to aggregate demand in most countries this year, but a tightening is projected to commence next year in G-20 emerging markets. Fiscal policy is projected to begin tightening in emerging G-20 economies next year, reflecting a combination of reduced anti-crisis spending and expected consolidation beyond the withdrawal of crisis-related stimulus in Brazil, Mexico, and Turkey, supported by a pick-up of growth. Higher commodity prices are also expected to contribute to lower overall deficit.